The Contribution of Human Resource Management Roles to Improving Organisational Effectiveness for South African State-Owned Enterprises - Dlamini, Bongani Innocent; Muzanenhamo, Arvid; Zogli, Luther-King Junior (Research Aspects in Arts and Social Studies Vol. 2, 2022)
Human Resource Management has experienced a paradigm shift in the way in which it assists organisations to achieve their goals. The change from personnel management to strategic human resource management has been accepted by industry gurus as it facilitates organisational competitiveness. In a dynamic business environment, Human Resource Management evolves to suit the new environment for organisational effectiveness. Human Resource Management roles are benefiting both private and public sector organisations. This paper explores the contribution made by human resource management roles to improving organisational effectiveness. This makes HRM professionals relevant and effective in organisations. The paper is a study carried out in a South African State-owned enterprise to examine the contribution of HRM roles. A qualitative research approach was applied using interviews for data collection from HR practitioners and departmental supervisors in a state-owned enterprise. Twenty-four participants were purposively selected to provide data for the study. The findings of this study showed that Human Resource Management roles benefit the organisation through a reduction in employee turnover, employee development, employee wellness and internal communication. These findings are relevant in today’s environment since companies are currently facing challenges such as brain drain, technological changes, competition and employee stress.